Pancreatic Tuberculosis Diagnosed by EUS: One Disease, Many Faces - Vafa, Haydeh; Arvanitakis, Marianna; Matos, Celso; Demetter, Pieter; Eisendrath, Pierre; Toussaint, Emmanuel; Hittelet, Axel Benoit; Deviere, Jacques; Delhaye, Myriam (JOP. Journal of the Pancreas, 2013)
Context Pancreatic/para-pancreatic tuberculosis is an extremely rare clinical entity even in endemic regions. It can present as a cystic or solid pancreatic mass mimicking pancreatic malignancy. There are no specific imaging criteria and the clinical symptoms remain vague. Therefore, most cases are diagnosed after surgical exploration for presumed pancreatic neoplasia. Case report We report five cases of pancreatic tuberculosis each time with a different clinical presentation, in an occidental country setting where the diagnosis was done by EUS guided FNA (EUS-FNA). Conclusion EUS-FNA is a safe and promising technique for the diagnosis of pancreatic/para-pancreatic tuberculosis, avoiding unnecessary surgery. Image: Space-occupying lesion with cellular proliferation.